2017
DOI: 10.17921/1415-5141.2016v20n2p99-106
|View full text |Cite
|
Sign up to set email alerts
|

Análise da Percepção de Estudantes e Funcionários Quanto a Inclusão e o Desenvolvimento Cognitivo de Alunos da Terceira Idade no Ambiente Universitário

Abstract: ResumoÉ comum encontrar pessoas da terceira idade no ambiente universitário e retornando ao mercado de trabalho. Visando entender como é a percepção dos outros alunos em relação aos idosos, foram entrevistadas 30 pessoas entre homens e mulheres na faixa etária de 18 a 60 anos na Universidade de Cuiabá -Unic, Campus Barão, a fim de identificar os fatores de manifestações de aprendizagem do aluno universitário na terceira idade. Foram aplicados questionários referentes aos fatores: emocional/social, cognitivo e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The participation of the elderly in educational activities has been related to positive consequences, such as the reduction of psychosomatic diseases [12][13][14][15][16][17][18][19] , the increase of cognitive reserve 12,30 and the consequent improvement in quality of life 12 . In the same context, it was found that participation in the U3A-Unifesp/BS made it possible to review what the participants had studied in their youth, to acquire new knowledge, to express one's own ideas, to listen and to be heard, and to put into practice the acquired learning, in an exercise of what is conventionally called lifelong education 12,15,19,30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participation of the elderly in educational activities has been related to positive consequences, such as the reduction of psychosomatic diseases [12][13][14][15][16][17][18][19] , the increase of cognitive reserve 12,30 and the consequent improvement in quality of life 12 . In the same context, it was found that participation in the U3A-Unifesp/BS made it possible to review what the participants had studied in their youth, to acquire new knowledge, to express one's own ideas, to listen and to be heard, and to put into practice the acquired learning, in an exercise of what is conventionally called lifelong education 12,15,19,30 .…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of intergenerational relationships in the third age should be emphasized 2 , as the interaction between the young and old in education programs encourages new perceptions and the renewal of expectations regarding the future 2,18 . Social groups such as U3As are therefore consecrated as an environment of integration in which education can be reaffirmed through new learnings and exchanges 12 , helping the elderly to improve their physical and mental quality of life, making them aware of the importance of self-care and self-worth, increasing their motivation and self-esteem and renewing their sense of citizenship 2,4.…”
Section: Education and Social Interaction In The Third Agementioning
confidence: 99%
See 1 more Smart Citation